METODE ANGELS SEBAGAI PENILAIAN TINGKAT KESEHATAN BANK SYARIAH DI INDONESIA - Hendra Syahputra; Hendrik Tri Oktaviansyah (Jurnal Ekonomi Syariah Darussalam, 2023)
This study aims to analyze the bank health assessment using ANGELS approach in Sharia Bank. This research uses a non-interactive qualitative approach that is an analysis research that conducts assessment based on document analysis and provides interpretation of a concept. Primary data is done by using structured interviews using prepared questionnaires, secondary data from this research are sharia financial report year 2016 in the form of ROA, ROE, CAR, NPF, LDR and MR. The results of this study indicate that the health assessment of Sharia Bank using ANGELS has a score of 86.79 so it is said to be healthy. The concept of ANGELS which consists of (Amanah Management, Non-Economic Wealth, Give Out, Earning, Capital and Asset, Liquidity and Sensitivity to Market and Economich Wealth) in practice needs to be done revision is indicators amanah management of accountability to God and accountability to nature because in practice these indicators are contrary to the concept practiced in the field. revision of accountability to God and accountability to nature is change into ihsan and tablig.